A study of the thermoelectric properties of benzo[1, 2-b:4, 5-b′]dithiophene–based donor–acceptor conjugated polymers. Issue 35 (8th August 2018) - Wang, Luhai; Pan, Chengjun; Chen, Zhongming; Zhou, Xiaoyan; Gao, Chunmei; Wang, Lei
Abstract : Three benzo[1, 2- b :4, 5- b ′]dithiophene (BDT)-based donor–acceptor (D–A) conjugated polymers with different side chains were designed, synthesized, and investigated as organic thermoelectric materials. Abstract : Three benzo[1, 2- b :4, 5- b ′]dithiophene (BDT)-based donor–acceptor (D–A) conjugated polymers with different side chains were designed, synthesized, and investigated as organic thermoelectric materials. Changing the side chains caused the three polymers to have different physical and chemical properties. The thermoelectric properties of BDT-based conjugated polymers have been systematically investigated through fine tuning of the side chains. Among the three polymers, the polymer with alkylthienothiophene moieties as the side chains exhibited the best thermal stability (thermal decomposition temperature above 400 °C), the highest electrical conductivity (1.519 S cm −1 ), and the largest Seebeck coefficient (413.79 μV K −1 ). The results of this study can guide the future design and synthesis of high-performance thermoelectric conjugated polymers.